2013
DOI: 10.1177/0300060513487627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ramosetron with combined ramosetron and midazolam for preventing postoperative nausea and vomiting in patients at high risk following laparoscopic gynaecological surgery

Abstract: Midazolam given at induction of anaesthesia or at the end of the surgery, combined with ramosetron, was more effective than ramosetron alone in reducing the incidence of PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…It indicated that 40 patients per group were required [25]. Assuming a potential dropout rate of 10%, the final sample size was set at 44 patients per group.…”
Section: Methodsmentioning
confidence: 99%
“…It indicated that 40 patients per group were required [25]. Assuming a potential dropout rate of 10%, the final sample size was set at 44 patients per group.…”
Section: Methodsmentioning
confidence: 99%
“…5 Similarly, Park and colleagues, in their study on 126 patients undergoing laparoscopic gynaecological surgeries, reported that incidence of complete response was around 70% with a combination of midazolam and ramosetron while it was 44% with ramosetron alone. 18 A few studies have examined the role of midazolam and dexamethasone in reducing PONV. 7,19 In children undergoing strabismus surgeries under general anaesthesia, Raid et al found that no child vomited when midazolam was used alone or in combination with dexamethasone as compared to 32% with dexamethasone alone.…”
Section: Ta B L Ementioning
confidence: 99%
“…The postulated antiemetic mechanism of midazolam includes glycine mimetic inhibitory effects, adenosinergic effects, and inhibition of dopamine release [21]. Midazolam may also affect striatal dopamine release, and the anesthetic actions of midazolam are partially related to inhibition of dopamine neuron A1 activity [22].…”
Section: Discussionmentioning
confidence: 99%